2014
DOI: 10.1007/s00232-014-9637-0
|View full text |Cite
|
Sign up to set email alerts
|

Transferrin Receptor-Mediated Endocytosis: A Useful Target for Cancer Therapy

Abstract: Current cancer management strategies fail to adequately treat malignancies with multivariable dose-restricting factors such as systemic toxicity and multi-drug resistance limiting therapeutic benefit, quality of life and complete long-term remission rates. The targeted delivery of a therapeutic compound aims to enhance its circulation and cellular uptake, decrease systemic toxicity and improve therapeutic benefit with disease specificity. The transferrin peptide, its receptor and their biological significance,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
182
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 254 publications
(191 citation statements)
references
References 124 publications
5
182
1
2
Order By: Relevance
“…207 It is reported that the mRNA level of TfR1 is upregulated in human HCC but that of TfR2 is downregulated. 208 Consistent conclusion has been drawn in a similar study on a rat model of HCC.…”
mentioning
confidence: 99%
“…207 It is reported that the mRNA level of TfR1 is upregulated in human HCC but that of TfR2 is downregulated. 208 Consistent conclusion has been drawn in a similar study on a rat model of HCC.…”
mentioning
confidence: 99%
“…During RMT, macromolecules move across the endothelial cells into the brain, due to the expression of several peptidespecific receptors, e.g. neonatal Fc receptor, [55] lowdensity lipoprotein receptor-related protein receptor, transferrin receptor, [56] lactoferrin receptor, [57] and insulin receptor.…”
Section: Preclinical Studies In Brain Tumorsmentioning
confidence: 99%
“…[14][15][16] This study reports on the design of a transferrin (Tf)-conjugated NGO nanosystem, which is a specific targeting molecule for oncotherapy. [17][18][19] Tf-NGO@Pt nanoparticles exhibit good water solubility through polyethylenimine (PEI) decoration. 20 Therefore, they offer a solution to the poor solubility of Pt complexes.…”
Section: Introductionmentioning
confidence: 99%